Fauna Tungau Macrochelidae (Mesostigmata: Acari) dan Asosiasinya dengan Kumbang Kotoran di Gunung Sawal, Ciamis, Jawa Barat - Hartini, Sri (Perhimpunan Biologi Indonesia, 2014)
Study of macrochelid mite: Mesostigmata: Acari has been done in Mt. Sawal Nature Reserve, Ciamis, West Java.Three genera, eight species of family Macrochelidae collected associated with scarabaeid dung beetles. Genera ofmites i.e., Holostaspella (H. oblonga Hartini & Takaku, 2010), Neopodocinum [N. bosschai (Berlese, 1901) and N.subjaspersi Hartini & Takaku, 2003] and Macrocheles [M. dispar (Berles, 1910)]; M. jabarensis Hartini & Takaku,2003; M. kraepelini (Berlese, 1905); M. pumilus Hartini, Dwibadra & Takaku, 2009 and M. sukabumiensis Hartini& Takaku, 2003]. Scarabaeid dung beetles assosiated with macrochelid mite reported three genera and 10 species,i.e., Catharsius, Copris and Onthophagus. The high value of niche overlap of two dung beetles O. (O.) orientalis andO. (O.) javaecola (96,97%) shows that the two beetle species are able to serve almost equally as transportation modefor the same species of macrochelid mites.Keywords: Macrochelid mite, Mt. Sawal, dung beetles